The Role of Social Support of Guidance and Counseling Teachers and Academic Resilience on Smartphone Addiction - Nasa, Almahbuban; Daulay, Nurussakinah (Jurnal Basicedu, 2022)
Smartphones are an alternative to distance learning media in the era of the Covid-19 pandemic. The presence of smartphones has both positive and negative sides to students. One of the negative aspects that are dangerous for students is smartphone addiction. This is based on the age of students (children or teenagers) who have not been able to objectively sort out the usefulness of something wisely. On this basis, the support role of BK teachers is needed in internalizing academic values to students. This study aims to determine the role of BK teacher's social support and academic resilience on smartphone addiction. This type of research uses guidance and counseling action research (PTBK), through a pre-test, post-test design model. The subjects of this study were 6 students of class IX MTs Kesuma LKMD Namorambe. The results of this study indicate that the role of BK teacher social support and academic resilience can reduce smartphone addiction in 6 grade IX students of MTs Kesuma LKMD Namorambe, this can be seen from the results of a significant comparison, starting from the pre-research stage 95%, the first cycle was 73 %, and obtained a low category in the second cycle of 45%.